Terminal relaxation of model poly(dimethylsiloxane) networks with pendant chains - Vega, Daniel Alberto (2001)
Stress relaxation of model poly(dimethylsiloxane) networks with pendant chains and nearly constant cross-linking density was studied. The networks were obtained by end-linking a mixture of long chains bearing terminal reactive groups with a trifunctional cross-linker. Long poly(dimethylsiloxane) chains in the initial mixture contain 90 wt % of difunctional molecules with reactive groups at both ends and 10 wt % of monofunctional chains with a single reactive terminal group located in one of their ends. Difunctional chains will be mainly elastically active chains after cross-linking while monofunctional chains will remain as long pendant molecules. The fitting of the experimental stress relaxation values to the classic Chasset-Thirion equation shows a strong dependence of the exponent on the molecular mass distribution of the pendant chains. From these results, a new model for the terminal relaxation of elastomers is proposed, taking into account the molecular mass distribution of pendant chains. The dynamics of polymer networks in the terminal relaxation zone is modeled considering the reptation theory. In the terminal zone, the proposed model behaves similarly to the Chasset-Thirion equation. The model adequately describes the behavior of networks synthesized by end-linking. On the other hand, when applied to different networks, it leads to similar conclusions as previous theories developed for networks obtained by random cross-linking.